Comparison of monoamine oxidase and selected heavy metal levels in the blood and the workplace among e-waste sorting workers in Ubon Ratchathani Province, Thailand - Kornwika Harasarn; Nantaporn Phatrabuddha; Pratchaya Kaewkaen; Wanlop Jaidee; Anamai Thetkathuek (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. E-waste sorting workers usually separate electronic waste. Therefore, they can be exposed to heavy metals. Objectives. This study compared monoamine oxidase (MAO) levels affected by the levels of lead (Pb), cadmium (Cd), and nickel (Ni) in the blood and their workplace among e-waste sorting workers (EWSW). Material and methods. The exposed group included 76 EWSW, and the non-exposed group included 49 village health volunteers. An interview form was used to assess the risk factors. We measured Pb, Cd, and Ni on the work surfaces and in the blood, and MAO levels as a neurological enzymes. Results. Among the EWSW, 42 were males (55.3%), and the mean age (SD) 48.0 (12.64) years, and income were 156.37 ± 88.08 USD. In the work areas of the exposed group, the concentration of Pb, Cd, and Ni were 245.042 (± 613.910), 0.375 (± 0.662), and 46.115 (± 75.740) μg/100 cm2, respectively, while the non-exposed group, the concentration of Pb, Cd, and Ni were 0.609 (± 0.934), 0.167 (± 1.171) and 1.020 (± 0.142) μg/100 cm2. Pb and Ni concentrations in the workplace of the exposed groups were statistically different from that of the non-exposed group. Pb, Cd, and Ni concentrations in serum were 6.411 ± 1.492 μg/dL, 0.9480 ± 0.350 μg/L, 2.568 ± 0.468 μg/L, respectively, while in the non-exposed group, the heavy metal concentrations were 6.411 ± 1.620 μg/dL, 0.909 ± 0.277 μg/L, 2.527 ± 0.457 μg/L. The MAO in the exposed group was 362.060 ± 97.981 U/L, while that in the non-exposed group was 369.771 ± 86.752 U/L. Moreover, MAO concentration was significantly different from Ni concentration (p < 0.05). Conclusion. The electronic waste sorting workers should clean their work areas to reduce the Pb, Cd, and Ni levels on the working surfaces, and health surveillance should be performed.